(untitled) (TAJ: Journal of Teachers Association, 2009)
Japanese encephalitis is numerically one of the most important causes of mosquito borne viral encephalitis not only in Asia but all over the world. Japanese encephalitis infection has not been recognized in Bangladesh since an outbreak in 1977 near Mymensingh. A prospective hospital based surveillance study carried out by Centre for Health and Population Research (ICDDR,B) and the Centers for Disease Control and Prevention (CDC), USA began in June 2003 at Dhaka, Mymenhsingh and Rajshahi Medical College Hospital to find out the causes of encephalitis proved that there are 6% patient who were admitted to the hospital with the sign and symptoms of encephalitis were infected with JE. In Rajshahi Medical College Hospital 12.38% encephalitic patients had JE infection. Though the study is ongoing but these data suggest that Japanese encephalitis virus is an emerging cause of encephalitis in Bangladesh. doi: 10.3329/taj.v17i1.3493 TAJ 2004; 17(1) : 57-70